Experimental osteoarthritis model by means of medial meniscectomy in rats and effects of diacerein administration and hyaluronic acid injection - Rezende, Marcia Uchôa; Hernandez, Arnaldo José; Oliveira, Claudia Regina Gomes Cardim Mendes; Bolliger Neto, Raul (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: The development of a slow and progressive mechanical model for osteoarthritis is important for correlation with clinical practice, and for evaluating the effects of disease-modifying medications. A mechanical osteoarthritis model was developed to evaluate the effects of intra-articular hyaluronic acid (HA) injection and oral diacerein administration. DESIGN AND SETTING: Experimental study at the Department of Orthopedics and Traumatology, Uni-versidade de São Paulo. METHOD: Total medial meniscectomy was performed on seven groups of ten Wistar rats each, com- prising four control groups (C) and three study groups (S). C.I: operated, non-medicated; C.II: operated, injections of HA vehicle; C.III: non-operated, non-medicated; C.IV: operated, non-medicated, sacrificed three months post-meniscectomy; S.I: operated, receiving intra-articular HA injections; S.II: operated, oral diacerein from the third to the seventh postoperative month; S.III: operated, received both medications. All the animals (except C.IV) were sacrificed seven months post-meniscectomy. All femurs and tibias were assessed histologically. RESULTS: The most severe degenerative histological changes were in the tibias of the operated knees. On the contralateral side, all groups had mild changes on the tibial surface. The femoral surface had slight changes. C.I showed severe changes. S.II results matched those of C.IV. HA protected the tibial surface. S.II and S.III had similar results. CONCLUSIONS: 1) The experimental model produced mild arthritis after three months and severe arthritis after seven months; 2) diacerein reduced the degenerative changes in both knees; 3) HA protected the joint cartilage; 4) Combining the two drugs did not improve the results.